PENGEMBANGAN PENDIDIKAN AKHLAK MELALUI PEMBERDAYAAN MANAJEMEN ORGANISASI PEMUDA - Ilham Andika Putra; Achadi Budi Santosa (Institut Agama Islam Negeri (IAIN) Tulungagung, 2021)
Abstract: Adolescent morality is the most strategic foundation for the nation's future development. The emergence of organizations that focus on moral development such as youth hijrah, better known as shift organizations, has attracted a lot of interest among young millennials to join them. The purpose of this study is to reveal the management of the hijrah youth organization in instilling moral education among adolescents. The approach is carried out through a qualitative approach using the literature review method (narrative literature review). This research reveals that hijrah youth organizations have used the strategy of planting branding images in managing their organizations. The organization's members are driven by a millennial youth, a community leader who is appointed as a driving figure for the moral improvement of young people. The implementation of shift organization management is carried out through; (1) the relationship between members is quite communicative, (2) the cool style of young people as branding in instilling a positive impression, (3) the selection of material content close to real life, and (4) blended learning educational methods.